Rendering historical and sociocultural references through subtitles: The case of English-Indonesian translation in Netflix’s History 101 - Amilia, Ika Kartika; Merrita, Diah (UNIB Press, 2025)
In today’s global circulation of audiovisual media, translating cultural references poses a significant challenge–particularly in documentary genres that aim to educate diverse audiences. History 101, a Netflix documentary series, features dense historical and cultural content that demands careful linguistic and cultural adaptation in its subtitled version. This study investigates the types of cultural references and the subtitling strategies used to translate them into Indonesian. Drawing on Cintas and Remael’s (2021) taxonomy–widely applied in audiovisual translation research–the study adopts a descriptive case study design. The analysis identifies a high concentration of ethnographic references, followed by socio-political and geographical categories. These references include elements such as daily life objects, institutions, and place names. To render these into the target language, the subtitler applies a range of strategies, with loan translation being the most frequently used. Literal translation, calque, explicitation, substitution, and transposition are also observed, reflecting a tendency to strike a balance between linguistic accuracy and accessibility for the target audience. Overall, the findings underscore the richness of the documentary’s cultural content and the complexity of subtitling such materials. The frequent use of ethnographic references and loan translation suggests an effort to preserve cultural specificity while ensuring comprehension for Indonesian viewers.